Handbook of Satellite Applications - Pelton, Joseph N.; Madry, Scott; Camacho-Lara, Sergio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The first edition of this ground breaking reference work was the most comprehensive reference source available about the key aspects of the satellite applications field. This updated second edition covers the technology, the markets, applications and regulations related to satellite telecommunications, broadcasting and networking-including civilian and military systems; precise satellite navigation and timing networks (i.e. GPS and others); remote sensing and meteorological satellite systems. Created under the auspices of the International Space University based in France, this brand new edition is now expanded to cover new innovative small satellite constellations, new commercial launching systems, innovation in military application satellites and their acquisition, updated appendices, a useful glossary and more.
From the Contents: Satellite Communications -- Satellite Applications Handbook: The Complete Guide to Satellite Communications, Remote Sensing, Navigation, and Meteorology -- Satellite Communications Overview -- History of Satellite Communications -- Space Telecommunications Services and Applications.-  Satellite Orbits for Communications Satellites -- Fixed Satellite Communications: Market Dynamics and Trends -- Satellite Communications Video Markets: Dynamics and Trends -- Mobile Satellite Communications Markets: Dynamics and Trends -- An Examination of the Governmental Use of Military and Commercial Satellite Communications -- Economics and Financing of Communications Satellites -- Satellite Communications and Space Telecommunications Frequencies -- Regulatory Process for Communications Satellite Frequency Allocations -- Satellite Radio Communications Fundamentals and Link Budgets -- Satellite Communications Modulation and Multiplexing -- Satellite Transmission, Reception and On-Board ProcessingSignaling and Switching -- Satellite Communications Antenna Concepts and Engineering -- Satellite Antenna Systems Design and Implementation Around the World -- Satellite Earth Station Antenna Systems and System Design -- Technical Challenges of Integration of Space and Terrestrial Systems.
Keywords: Aerospace engineering; Astronautics; Physics; Geographic information systems; Chemistry -- Data processing; Solar system; Telecommunication; Aerospace Technology and Astronautics; Applied and Technical Physics; Geographical Information System; Computational Chemistry; Space Physics; Communications Engineering, Networks